MENGINTIP WISATA SYARIAH DI PULAU SANTEN BANYUWANGI - M. Amir Mahmud; Muhammad Endy Fadlullah (Ulumuna: Jurnal Studi Keilsman, 2019)
This paper aims to explain that the phenomenon of syariah tourism in Santen Island Banyuwangi District was not always directly proportional to the ideal concept proposed by the government of Banyuwangi district. This research is a descriptive research whichtaken from qualitative data in the form of field observation, interview, and documentation as the material of analysis, so writer can find important findings. First, the big concept that is carried by the government of Banyuwangi district has not been able to be realized properly such as tourism management that has not shown syariah, lack of good understanding of the concept of syariah tourism by managers, facilities are not adequate, human resources are still low, the values ​​of syariah aspired has not materialized, and there is no exact difference between syariah tours with conventional tourism or more precisely "syariah tour of conventional tourism". Secondly most of the visiting tourists are not satisfied and feel disappointed with the implementation of syariah tourism because they met less criteria of syariah that they expected.